Edukasi Membangun Jejaring Bisnis Untuk Meningkatkan Potensi Usaha Petani Jagung di desa Limang Kecamatan Tiga Binanga Kabupaten Karo - Junita, Audia; Sari, Ade Indah; Diansyah, T. Moh. (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This community service activity is in the form of education to increase the knowledge of corn farmers regarding the importance of building business networks to increase the business potential of corn farmers in Limang Village, Tiga Binanga District, Karo Regency. Submission of material is done using power point software, infocus and LCD. From the results of the pre-test and post-test questionnaire data analysis, it is known that the understanding of corn farmers in Desa Limang Kecamatan Tiga Binanga Kabupaten Karo has increased from before being given educational activities. The renewal of knowledge and innovation of corn farmers for the adoption of various knowledge, technology and various other managerial activities must be carried out continuously in developing corn farmers' crops, especially in Desa Limang Kecamatan Tiga Binanga Kabupaten Karo